New and little known species of Erasmoneura Young (Hemiptera: Cicadellidae: Typhlocybinae) - Dmitriev, D. A. (Zootaxa, 2008)
The North American leafhopper genus Erasmoneura Young was described as a subgenus of Erythroneura Fitch by Young (1952) to comprise the informal Erythroneura vulnerata Fitch species group previously recognized by Beamer (1938, 1946). Erasmoneura was recently elevated to generic status (Dietrich & Dmitriev, 2006) and revised (Dmitriev & Dietrich, 2007). In this paper, the male of Erasmoneura bipentagona (Beamer), previously known only from the female holotype and placed in the genus based on external similarity and features of wing venation (Young, 1952; Dietrich & Dmitriev, 2006; Dmitriev & Dietrich, 2007, see also the note for the species below), and a new species are described. A key for identification of all 13 species of the genus is provided. The key is based mainly on male genitalia characters. Although individual species have a characteristic color pattern, details and intensity may be highly variable both inter- and intraspecifically.